CIPP Model Approach to School-Based Management Program Evaluation - Musifuddin Musifuddin; Dukha Yunitasari; Hary Murcahyanto (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2024)
This study is an evaluative study using the CIPP model to evaluate the effectiveness of implementing the School-based Management program at the 1 Sukasada State High School. The subjects involved 70 respondents, including the head of the school, teachers, entrepreneurs, students, and school committees. Data processing is performed in a descriptive quantitative manner with simple statistical analysis and tabulation, following the National Department of Education standards. The results showed a context component score of 2,973, an input of 3,604, a process of 2,892, and a product (output and outcomes) of 2,495. The results of the observations show that the conditions of the community and the potential of the area are very supportive of the development of schools. However, of the 483 alumni, only 230 (46.75%) were traceable, with 27.39% working according to competence and 20.87% continuing education. Low output quality is affected by the efficiency of processes, contexts, and inputs, resulting in low school performance efficiency scores. Thus, the effectiveness of the implementation of School-based Management in the State High School 1 Sukasada was assessed as unsatisfactory. It is recommended that managers improve planning, consider market needs, and improve the effectiveness of implementation and evaluation of School-Based Management programs in the school.